2019
DOI: 10.1111/zph.12654
|View full text |Cite
|
Sign up to set email alerts
|

Recent rapid changes in the spatio‐temporal distribution of West Nile Neuro‐invasive Disease in Italy

Abstract: In Italy, the first human case of West Nile Virus (WNV) infection was reported in 2008 and, since then, the number of cases has been steadily increasing. In this study, we describe the temporal and spatial pattern of WNV infection risk among humans in Italy, focusing on the human cases of West Nile Neuro‐invasive Disease (WNND) observed between 2008 and 2017. Incidence rates are estimated for each year and province under study. The incidence temporal trend is estimated using Poisson regression, and a spatio‐te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 29 publications
4
21
0
Order By: Relevance
“…The spatial model (Fig 3) is in accordance with other studies that reported a high prevalence of WNF within the Danube and Po basins [12,55]. The Danube basin constitutes an important settlement area for migratory birds from Europe, Asia and Africa, and consequently a concentration area for the pathogens carried by migrant birds during their routes along the stopover and feeding areas [56].…”
Section: Spatial Risk Modelsupporting
confidence: 87%
“…The spatial model (Fig 3) is in accordance with other studies that reported a high prevalence of WNF within the Danube and Po basins [12,55]. The Danube basin constitutes an important settlement area for migratory birds from Europe, Asia and Africa, and consequently a concentration area for the pathogens carried by migrant birds during their routes along the stopover and feeding areas [56].…”
Section: Spatial Risk Modelsupporting
confidence: 87%
“…Data collection: In 2011, national surveillance plan for WNV infections was extensively revised, implementing the publication of periodic surveillance bulletins [ 17 , 19 , 28 ]. Periodic bulletins (available from: ; accessed on 23 April 2021) include the following data: total number of WNV infections reported during the surveillance season (i.e., 15 June to 15 November) irrespective of their actual clinical features, number of WNV infections identified in blood donors, number of WNND cases (both as a total estimate and stratified by province, age group, and month of diagnosis).…”
Section: Methodsmentioning
confidence: 99%
“…Even though the inception of WNV occurred quite lately when compared to other European countries (i.e., 2008), currently Italy includes some among the most heavily affected areas in the European Union. Not coincidentally, in 2010, the Italian Ministry of Health implemented the first National WNV surveillance plan, which integrated veterinary, entomological, and epidemiological data in order to more efficiently monitor the spread of WNV and detect human cases of WNV infection [ 16 , 17 , 18 , 19 , 20 ]. Some earlier reports on the integrated surveillance system have been published [ 16 , 17 , 18 , 19 , 20 ], but all of them predates the transmission season of 2018, in which 1605 confirmed cases reported across European countries nearly doubled the total cases registered in the previous three years combined [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations